Targeting PRMT5 protein-protein interactions with peptidic modulators - Krzyzanowski, Adrian (Technische Universität Dortmund, 2022)
Protein arginine methyltransferase 5 (PRMT5) is an important enzyme, methylating arginine residues of its substrates. PRMT5 is involved in a very large number of various cellular process, and has strong ties to a plethora of health disorders. PRMT5 mediates a number of protein-protein interactions (PPIs) with diverse adaptor proteins, such as the obligate binding partner MEP50, and adaptor proteins RioK1, pICln and COPR5. Modulation of PRMT5 PPIs appears as an attractive alternative to the inhibition of the active methylation site, giving an opportunity for significantly more precise targeting of the PRMT5 functionality in cells. This thesis describes pathways for development of peptidomimetics intended for the inhibition of various PPIs formed by PRMT5 or its adaptor protein MEP50. PPI between PRMT5 and MEP50 was investigated using available structural data to design inhibitory peptides. The compounds were synthesised and evaluated using biophysical and enzymatic assays. None of the synthesised compounds showed any activity in the employed assays. In the second part, the thesis describes the analysis of a potential PPI between SUZ12 and MEP50. A number of SUZ12 fragments spanning different protein regions were synthesised and tested for the direct interaction with the PRMT5-MEP50 complex. The analysis indicated that the short SUZ12 sequence CPWCTL is responsible for the interaction with the methyltransferase complex. Further analysis with the binding sequence and control proteins showed very strong non-specific interactions. In light of the obtained results any further peptidomimetic development based on the SUZ12 sequence was not pursued. The final chapters of the thesis focus on the PPIs between PRMT5 and adaptor proteins RioK1, pICln and COPR5. A consensus sequence GQF[D/E]DA[D/E], identified in the terminal regions of the adaptor proteins, was determined to be responsible for mediating the interactions with PRMT5. Biophysical assays and X-ray crystallography allowed to characterise the binding interface and revealed that the consensus sequence binds to the non-catalytic TIM barrel domain of PRMT5. The biophysical data were then used for the design of highly stable macrocyclic PRMT5 adaptor protein interaction inhibitors. Optimisation of the molecular structure resulted in a potent cyclic PRMT5 binder (KD = 89 nM). The developed molecule could inhibit the PPI between PRMT5 and full length pICln when tested in vitro (IC50 = 654 nM). Examination of the compound activity in cellular lysates revealed a surprising selectivity towards the inhibition of the PRMT5 interactions with RioK1 over the interactions with pICln. The developed compound did not supress the enzymatic activity of the methyltransferase and did not inhibit the interaction with MEP50.
Keywords: PRMT5; Peptides; Macrocycles; Cyclopeptides; Protein-protein interaction; Inhibitors; 570; 540; Makrocyclen; Peptide